UJI AKTIVITAS ANTI BAKTERI EKSTRAK ETANOL DAUN PANDAN WANGI (Pandanus amaryllifolius Roxb) TERHADAP BAKTERI PENYEBAB DIARE - Jacky, Jacky; Putri, Dea Anggi; Azizah, Masayu (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2019)
Diarrhea is still a major problem in children's health, especially in developing countries like Indonesia.. One of alternative medicine that have potential as antibacterial is pandan wangi leaves. This study aims to knowing effect of pandan wangi leaves ethanol extract as an antibacterial against. The design of this study was experimental. The antibacterial activity was determined by agar diffusion method with concentration extract respectively 40%, 50%, 60%, cotrimoxazole as positive control. The result of the research shows that etanol extract of pandan wangi leaves has the antibacterial effect to Bacillus cereus ATCC 11778 with inhibition capability 7,90 mm, 8,90 mm, 10,13 mm, 12,3 mm. Enterococcus faecalis ATCC 29212 8,10 mm, 9,26 mm, 10,20 mm, 12,2 mm. Shigella dysentri ATCC 11835 8,56 mm, 8,80 mm, 11,90 mm, 13,3 mm. Vibrio cholerae ATCC 14033 8,16 mm, 9,10 mm, 11,20 mm, 12,2 mm. Escherichia coli ATCC 25922 8,16 mm, 9,63 mm, 11,85 mm, 13,0 mm. Extract concentration that giving the most optimal inhibition capability to bacteria that causes diarrhea is concentration 60%. Key word : Pandan Wangi leave, antibacterial, Diarrhea